Originally Posted by
Bacterius Basically, if you have $\displaystyle f(x)$ as $\displaystyle x \rightarrow f(x)$, then $\displaystyle f(x)^{-1}$ is $\displaystyle f(x) \rightarrow x$.
The first one is pretty straightforward : you are asked to find $\displaystyle f(1)^{-1}$ when $\displaystyle f(x) = x^2$.
Say $\displaystyle f(x) = y$, you have $\displaystyle y = x^2$. Express $\displaystyle x$ in terms of $\displaystyle y$, thus $\displaystyle x = \sqrt{y}$ or $\displaystyle x = - \sqrt{y}$. Therefore, $\displaystyle f(x)^{-1} = \sqrt{x}$ or $\displaystyle - \sqrt{x}$. Substitute : $\displaystyle f(1)^{-1} = 1$ or $\displaystyle -1$
I don't get b), though, what do you mean by the interval ?